2016
DOI: 10.5902/2179460x18875
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação Do Processo De Compostagem Utilizando Lodo De Estação De Tratamento De Efluentes De Laticínio

Abstract: Resumo O estudo avaliou o processo de compostagem utilizando lodo flotado da Estação de Tratamento de Efluentes de

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 1 publication
1
4
2
Order By: Relevance
“…[64] According to the NI n o 25/2009 (MAPA), for soil application the biocompost must present a minimum content of 1% (10 g kg À1 ) of Ca, therefore, the biocompost produced does not meet this condition. Rodrigues et al [34] studies the composting of floated sludge in a dairy effluent treatment plant and observed that, after the maturation of the biocompost, the concentrations of Ca were 0.7%, close value to that obtained in this work, which was 5.17 g kg À1 , corresponding to 0.51% of Ca at the end of the process.…”
Section: Parameterssupporting
confidence: 83%
See 3 more Smart Citations
“…[64] According to the NI n o 25/2009 (MAPA), for soil application the biocompost must present a minimum content of 1% (10 g kg À1 ) of Ca, therefore, the biocompost produced does not meet this condition. Rodrigues et al [34] studies the composting of floated sludge in a dairy effluent treatment plant and observed that, after the maturation of the biocompost, the concentrations of Ca were 0.7%, close value to that obtained in this work, which was 5.17 g kg À1 , corresponding to 0.51% of Ca at the end of the process.…”
Section: Parameterssupporting
confidence: 83%
“…In this study, Al and Na presented removals of 35% and 21.01% at the end of the process. Rodrigues et al [34] obtained Na concentrations of 0.02%, a value below that found in this study, which was 0.15%, although still being a low value according to the authors. The NI n o 25/2009 (MAPA) does not establish a maximum level for sodium in the organic fertilizers.…”
Section: Parameterscontrasting
confidence: 81%
See 2 more Smart Citations
“…Rodrigues et al (2016) ratifies the result as adequate, because according to him, the system in the process of composting should reach temperatures of 45 to 65 °C in the first days of activity, these values being indicative of satisfactory conditions of nutrient balance.…”
Section: Resultsmentioning
confidence: 99%